Descriptive Research on Municipal Bond Market with Environmental, Social and Governance Components for Economic Growth in Malaysia - Gardner, Huw Samuel (2023)
This thesis aims to investigate the potential of a Malaysian municipal bond market that incorporates components of ESG financing to accelerate economic development in Malaysia. The research covers the literature on bond markets and the important position they play in facilitating economic growth. Specifically, the role of municipal bonds as a vehicle for infrastructure financing and the increasing influence of ESG principles. The study developed a conceptual framework of four independent variables: bond issuance, credit rating, interest rate, and market infrastructure, with investor demand as the mediating variable and risk management as the moderating variable. This was represented as conceptual framework whereby six hypotheses were constructed based on this. Literature for all the constructs were gathered from 2018 until 2023 comprehensively. This research covered the literature in Malaysian bond market and global bond market. This research adopted a mixed-method approach as suggested in literature. Sample of 201 respondents were considered based on Krejcie and Morgan's sample size formula. Non-random sampling technique was adopted to select the samples. Atlas.ti is used for the qualitative analysis while SmartPLS was used for the quantitative analysis. Mind mapping, word cloud and mind tree were part of qualitative analysis. Structural and measurement model were executed in quantitative analysis. The study's six hypotheses are all positive, and the results show that ESG financing can positively impact the economic development of Malaysia. This research provides insights and recommendations for policymakers, investors, and financial institutions to leverage ESG financing for sustainable economic growth in Malaysia. Interpretivism Research Philosophy was concluded as the research had mix method approach in the epistemology point of view.